Social Inclusion and Constitutional Justice: Reassessing Equality and Affirmative Protection in Indonesia - Ismail Hasani; Sayyidatul Insiyah; Halili Halili (Faculty of Law, Universitas Sebelas Maret, 2026)
Social inclusion has emerged as a significant subject in development governance. Yet, its constitutional base within Indonesia’s legal framework remains inadequately examined, especially during periods of political leadership transition. The article examines the constitutional foundation of social inclusion as delineated in the 1945 Constitution of the Republic of Indonesia. It assesses its execution during the initial phase of President Prabowo Subianto’s administration. This study employs a literature-based methodology alongside a normative-constitutional and philosophical framework to analyse constitutional provisions, statutory frameworks, policy texts, and empirical data sourced from national and worldwide social inclusion indices. The findings reveal that social inclusion is a constitutional imperative grounded in Pancasila, expressed through comprehensive assurances of equality, non-discrimination, and proactive safeguarding for marginalised groups. Nonetheless, empirical data indicate ongoing structural exclusion impacting women, individuals with disabilities, religious or belief minorities, and indigenous populations. The article enhances legal study by reframing social inclusion as a mandatory constitutional duty rather than an optional policy initiative, while providing a cohesive analytical framework that connects constitutional law, human rights, and inclusive governance. The study focuses on the imperative of integrating inclusive governance as a fundamental legislative norm to promote substantial social justice in Indonesia.